An overview of COST Action TU1406, quality specifications for roadway bridges (BridgeSpec) - Matos, José C. (2017)
Publicado em "Life-cycle of engineering systems: emphasis on sustainable civil infrastructure: proceedings of the Fifth International Symposium on Life-Cycle Civil Engineering (IALCCE 2016), ISBN 978-1-138-02847-0"